The Effect of Emotional Abuse on Periodontal Status and Salivary Resisti - Sami, Qabas F.; Diab, Ban S. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Emotional abuse is a widespread form of child abuse. It is suggested that the adverse outcomes from all forms of abuse mostly result from the emotional impacts. Resistin, a polypeptide high in cysteine, can serve as a valuable biochemical indicator of periodontal tissue damage when detected in the saliva.Objective: To assess the relationship of emotional abuse with periodontal status and salivary resistin levels.Patients and Methods: This cross-sectional comparative study included 522 intermediate school students aged 13-15 years in Kirkuk/Iraq. Information on emotional abuse was obtained using Glaser criteria which is a self-administered, structured, questionnaire form. The levels of emotional abuse were categorized into mild (score between 24-26), moderate (score between 27-42), and severe (score between 43-72). Periodontal health was assessed by using the community periodontal index (CPI). Non-stimulated saliva was collected and salivary resistin levels were evaluated using an enzyme-linked immunosorbent assay (ELISA).Results: The most common level of abuse was moderate. The largest percentages of participants with dental calculus were observed in moderate (48.2%) and severe (57.5%) abuse groups and the highest mean number of sextants with gingival bleeding was observed in participants who experienced a moderate level of abuse (0.34). While the level of resistin was higher in the mild abuse group (237.06), all of its relationships with the periodontal condition were non-significant.Conclusion: Emotional abuse affects salivary resistin levels but has no obvious effect on periodontal status. Non-significant correlations were observed between salivary resistin levels and the levels of abuse with periodontal conditions.